Seeing is believing: Using crop pictures in personalized advisory services - Ceballos, Francisco; Foster, Tim; Hufkens, Koen; Jadhav, Arun; Kannan, Samyuktha; Kramer, Berber (International Food Policy Research Institute, 2018)
We developed, implemented, and evaluated an innovative personalized advisory service that complements picture-based insurance (PBI), an easy-to-understand low-cost insurance product for visible crop damage. We sent personalized agricultural advice based on real-time observations of crop conditions, from sowing to harvest, from farmers’ pictures of their insured plots. Such a service can empower data-driven farming through three channels: experts can tar-get messages to a farmer’s individual situation, thus increasing the value and timeliness of the advice; the tangibility of pictures in-creases ownership and take-up of the advice; and the service allows insurers to gather more monitoring data and provide recommendations on how to minimize risk, thus lowering expected insurance payouts.